IoT-Based Dashboard System for Real-Time Monitoring and Rule-Based Leakage Alerting in CPO Tank Truck Distribution - Abud Jabidi; Andi Prayogi; Muhammad Akbar Syahbana Pane (Journal of Digital Technology and Computer Science, 2026)
Purpose – Crude Palm Oil (CPO) distribution using tanker trucks faces challenges including delayed reporting, limited visibility, and potential cargo losses due to leakage or human error. This study develops an IoT-based dashboard for real-time monitoring and threshold-triggered leakage alerting during CPO distribution. Methods – A prototype was developed and tested in a controlled laboratory-scale environment. The system integrated an ESP32 microcontroller with a YF-S201 flow sensor, HC-SR04 ultrasonic level sensor, and NEO-6M GPS module. Sensor data were transmitted via MQTT, visualized on a web dashboard, and stored in a Supabase cloud database for historical tracking and operational review. Findings – Testing showed average error rates of 2.48% for the flow sensor and 2.67% for the ultrasonic level sensor. The GPS module captured location data across all test points. The system supported four simulated distribution phases: Loading, Transportation, Unloading, and Completed. During Transportation, a leakage alert was generated when outward flow was detected, confirming that the rule-based alert mechanism operated according to predefined logic. Research Implications – The system offers a prototype framework for improving transparency, traceability, and operational monitoring in CPO logistics. However, field validation using industrial-grade sensors and full-scale tanker truck deployment is required. Originality – This study integrates flow monitoring, tank level measurement, GPS tracking, cloud storage, and rule-based leakage alerting in a single IoT dashboard for CPO tank truck distribution.